Peningkatan Kualitas Layanan Penumpang Menggunakan Standar Penilaian Pelayanan Angkutan Perdesaan - Andari, Tania; Masbiran, Vivi Ukhwatul Khasanah; Momon, Momon; Savira, Evi Maya; Yolarita, Elsa; Manoby, Worry Mambusy; Asriani, Asriani (Research and Development Agency Ministry of Home Affairs, 2022)
In recent years, the government has been aggressively inviting the public to use public transportation for all regional residents in Indonesia. Mattson et al. (2021) stated that transportation and accessibility in the village are more comprehensive and have more complex transportation issues. Therefore, this study was conducted to measure rural transportation services to improve public transportation performance in the Pringsewu Regency. This study uses a mixed-method and combines quantitative and qualitative data at one time (Creswell, 2014). The data is analyzed quantitatively and then explained based on existing conditions and provisional assumptions. The data used are primary and secondary data. Primary data was obtained through field surveys on four rural transportation routes in Pringsewu Regency to obtain data on load factors, vehicle speed, waiting time, travel time, frequency/hour, and the number of vehicles operating from each route. Furthermore, the data is evaluated and given an assessment based on the suitability of indicators based on the assessment standard from the Directorate General of Land Transportation, Ministry of Transportation. Secondary data was obtained from Statistics Indonesia publications, official documents, and government websites. The analysis results showed that rural transportation services in the Pringsewu regency were below the ideal standard (70%), with an average loading factor of 40—50%, which is included in the bad category. This is estimated to be influenced by several factors, namely the low level of load factor and headway. The recommendation put forward is the need for efforts to add headways and increase the speed of travel time and reduce the frequency of trips to improve transportation performance.